Solar cell modules

By disconnecting the hole barrier layer in the solar cell module and keeping the hole transport layer continuous, the problem of low illuminance output reduction after high illuminance is solved, and output stability and photosensitive compound protection are achieved under low illuminance before and after high illuminance .

CN111989792BActive Publication Date: 2024-12-13RICOH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980026639.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-03-19
Filing Date
2019-02-19
Publication Date
2024-12-13
Estimated Expiration
2039-02-19

AI Technical Summary

Technical Problem

After exposure to high light illumination, the output of existing solar cell modules is significantly reduced at low light illumination, and the photosensitive compounds are easily destroyed, making it difficult to maintain high output under low light conditions indoors.

Method used

A solar cell module is designed in which the hole barrier layer between at least two adjacent photoelectric conversion elements is not connected, while the hole transport layer is in a continuous state to avoid current leakage under high illumination and be patterned by laser The gap formed covers the protective photosensitive compound.

Benefits of technology

It effectively suppresses current leakage and damage to photosensitive compounds caused by high illumination, ensures output stability at low illumination before and after high illumination, and can maintain high power output under indoor light sources such as LEDs and fluorescent lamps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111989792B_ABST
    Figure CN111989792B_ABST
Patent Text Reader

Abstract

A solar cell module including photoelectric conversion elements is provided, wherein each photoelectric conversion element includes a first substrate and a first electrode on the first substrate, a hole blocking layer, an electron transport layer, a hole transport layer, a second electrode and a second substrate, and a sealing member between the first substrate and the second substrate, and wherein in at least two photoelectric conversion elements adjacent to each other, the hole blocking layer does not extend to each other, but the hole transport layer is in a state of a continuous layer, wherein the hole transport layer extends to each other.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to solar cell modules. Background Art

[0002] In recent years, solar cells have become increasingly important as an alternative energy source to fossil fuels and as a measure to combat global warming. In addition, in recent years, solar cells that can efficiently generate electricity with light of low illuminance and be used indoors have received widespread attention. Specifically, the latter solar cells are expected to be used in a wide range of applications as self-sustaining power sources that do not require battery replacement or power wiring.

[0003] As photoelectric conversion elements for indoor use, amorphous silicon solar cells and dye-sensitized solar cells are known. Among them, dye-sensitized solar cells are advantageous in terms of cost reduction because they can be produced using a printing method known in the art. Generally, dye-sensitized solar cells have problems with evaporation or leakage of electrolyte liquid because the electrolyte liquid is encapsulated therein. However, in recent years, solid dye-sensitized solar cells using p-type semiconductor materials have been developed and attracted attention.

[0004] In order to improve the durability of the solid dye-sensitized solar cell module, it is important to protect the photosensitive compound adsorbed on the surface of titanium oxide from moisture and oxygen present in the sealed space or exhaust gas generated by the sealing resin. For example, PTL 1 discloses a solar cell module in which the durability of the solar cell module is improved by providing an ultraviolet absorbing material or a protective film in the sealed space.

[0005] Citation List

[0006] Patent Literature

[0007] PTL 1: Japanese Unexamined Patent Application Publication No. 2014-143333 Summary of the invention

[0008] Technical issues

[0009] An object of the present disclosure is to provide a solar cell module capable of preventing a decrease in output under light of low illuminance before and after exposure to light of high illuminance.

[0010] Technical solutions to the problem

[0011] According to one aspect of the present disclosure, a solar cell module includes a plurality of photoelectric conversion elements. Each photoelectric conversion element includes a first substrate, a first electrode, a hole blocking layer, an electron transport layer, a hole transport layer, a second electrode, a second substrate, and a sealing member. A first electrode, a hole blocking layer, an electron transport layer, a hole transport layer, a second electrode, and a second substrate are formed on the first substrate, and the sealing member is disposed between the first substrate and the second substrate. In at least two photoelectric conversion elements adjacent to each other, the hole blocking layer does not extend to each other, but the hole transport layer is in a continuous layer state, wherein the hole transport layer extends to each other.

[0012] Advantageous Effects of the Invention

[0013] The present disclosure can provide a solar cell module that can prevent a decrease in output under light of low illuminance before and after exposure to light of high illuminance. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a schematic diagram illustrating one example of the photoelectric conversion element of the present disclosure.

[0015] Figure 2 is a schematic diagram illustrating another example of the photoelectric conversion element of the present disclosure.

[0016] Figure 3 is a schematic diagram illustrating another example of the photoelectric conversion element of the present disclosure.

[0017] Figure 4 is a schematic diagram illustrating another example of the photoelectric conversion element of the present disclosure.

[0018] Figure 5 is a schematic diagram illustrating one example of a solar cell module of the present disclosure.

[0019] Figure 6 is a schematic diagram illustrating one example of a solar cell module of the present disclosure.

[0020] Figure 7 is a schematic diagram illustrating one example of a solar cell module of the present disclosure. DETAILED DESCRIPTION

[0021] (Solar cell module)

[0022] The solar cell module of the present disclosure includes a plurality of photoelectric conversion elements. Each photoelectric conversion element includes a first substrate, a first electrode, a hole blocking layer, an electron transport layer, a hole transport layer, a second electrode, a second substrate and a sealing member. The first electrode, the hole blocking layer, the electron transport layer, the hole transport layer, the second electrode and the second substrate are formed on the first substrate, and the sealing member is arranged between the first substrate and the second substrate. In at least two photoelectric conversion elements adjacent to each other, the hole blocking layer does not extend to each other, but the hole transport layer is in a continuous layer state, wherein the hole transport layers extend to each other.

[0023] The solar cell module of the present disclosure is completed based on the insights related to the following problems: the output of the solar cell module known in the prior art is significantly reduced with light of low light intensity (for example, indoor light after the solar cell is exposed to light of high light intensity (such as sunlight)). Specifically, the insights are as follows. Since the solar cell modules known in the art have hole blocking layers connected together, which leads to current leakage of light of high light intensity, when the solar cell module is used as a self-sustaining power source for sensors, etc., if the solar cell module is exposed to light of high light intensity even only once, it is difficult to obtain high output with light of low light intensity. In addition, in the case of a film forming a hole blocking layer after patterning the first electrode with a laser, the gap formed by the patterning cannot be fully covered by the hole blocking layer. Therefore, the photosensitive compound is easily destroyed by light of high light intensity. Therefore, it is difficult to obtain high output with light of low light intensity.

[0024] In at least two adjacent photoelectric conversion elements in the solar cell module of the present disclosure, the hole blocking layers are not connected together, but the hole transport layers are connected together. Therefore, the solar cell module of the present disclosure hardly causes current leakage due to light of high illuminance, and the photosensitive compound is not easily damaged, so the output reduction under light of low illuminance before and after exposure to light of high illuminance can be suppressed. Therefore, the solar cell module of the present disclosure can have high power output even after exposure to sunlight by using light emitted by lighting devices (e.g., light emitting diodes (LEDs) and fluorescent lamps) used indoors.

[0025] The solar cell module of the present disclosure includes a plurality of photoelectric conversion elements in which hole blocking layers do not extend to each other, but hole transport layers in at least two photoelectric conversion elements adjacent to each other are in a state of a continuous layer in which the hole transport layers extend to each other.

[0026] Next, the photoelectric conversion element will be described.

[0027] <Photoelectric conversion element>

[0028] The photoelectric conversion element is an element capable of converting light energy into electric energy, and has been applied to solar cells or photodiodes.

[0029] The photoelectric conversion element includes a first substrate, a first electrode, a hole blocking layer, an electron transport layer, a hole transport layer, a second electrode, a second substrate, and a sealing member.

[0030] The First Substrate

[0031] The shape, structure, and size of the first substrate are not particularly limited and may be appropriately selected depending on the intended purpose.

[0032] The material of the first substrate is not specifically limited, and can be appropriately selected according to the intended purpose, as long as the material is a material with translucency and insulation. Examples of materials include substrates such as glass, plastic films and ceramics. In the examples listed above, in the case where the electron transport layer is formed as described below and a firing step is included at the same time, it is preferred to have a substrate with heat resistance to the firing temperature. In addition, the first substrate is preferably a flexible substrate.

[0033] The First Electrode

[0034] The shape and size of the first electrode are not particularly limited and can be appropriately selected depending on the intended purpose.

[0035] The structure of the first electrode is not particularly limited and can be appropriately selected depending on the intended purpose. The structure of the first electrode may be a single-layer structure or a structure in which a plurality of materials are laminated.

[0036] The material of the first electrode is not particularly limited and may be appropriately selected depending on the intended purpose, as long as the material is a material having transparency and conductivity to visible light. Examples of the material include transparent conductive metal oxides, carbon, and metals.

[0037] Examples of transparent conductive metal oxides include indium tin oxide (hereinafter referred to as "ITO"), fluorine-doped tin oxide (hereinafter referred to as "FTO"), antimony-doped tin oxide (hereinafter referred to as "ATO"), niobium-doped tin oxide (hereinafter referred to as "NTO"), aluminum-doped zinc oxide, indium zinc oxide and niobium titanium oxide.

[0038] Examples of carbon include carbon black, carbon nanotubes, graphene, and fullerene.

[0039] Examples of metals include gold, silver, aluminum, nickel, indium, tantalum, and titanium.

[0040] The examples listed above may be used alone or in combination. Among the examples listed above, transparent conductive metal oxides having high transparency are preferred, and ITO, FTO, ATO, and NTO are more preferred.

[0041] The average thickness of the first electrode is not specifically limited and can be appropriately selected according to the intended purpose. The average thickness of the first electrode is preferably 5 nm or more but 100 microns or less, more preferably 50 nm or more but 10 microns or less. In the case where the material of the first electrode is carbon or metal, the average thickness of the first electrode is preferably an average thickness with easy translucency.

[0042] The first electrode may be formed by methods known in the art, such as sputtering, vapor deposition, and spraying.

[0043] In addition, it is preferable to form the first electrode on the first substrate. A commercial product of a first electrode that is preliminarily formed on the first substrate and integrated with the first substrate may be used.

[0044] Examples of integrated commercial products include FTO coated glass, ITO coated glass, zinc oxide / aluminum coated glass, FTO coated transparent plastic film, and ITO coated transparent plastic film. Another example of an integrated commercial product includes: a glass substrate with a transparent electrode in which tin oxide or indium oxide is doped with cations or anions of different atomic values; and a glass substrate with a metal electrode having a light-transmitting structure, such as in the form of a mesh or stripes.

[0045] The above-listed examples may be used alone, in combination, or in a stacked form. In addition, metal wires may be used to reduce resistance.

[0046] Examples of the material of the metal wire include aluminum, copper, silver, gold, platinum, and nickel.

[0047] For example, metal wires are used in combination and formed on a substrate by vapor deposition, sputtering, or pressure bonding, and then an ITO or FTO layer is disposed on the metal wires.

[0048] Hole blocking layer

[0049] A hole blocking layer is formed between the first electrode and the electron transport layer. The hole blocking layer is configured to transfer electrons generated by the photosensitive compound and transferred to the electron transport layer to the first electrode and prevent contact with the hole transport layer. The presence of the hole blocking layer can inhibit the flow of holes into the first electrode and prevent low output caused by the recombination of electrons and holes. Compared with a fluid-type photoelectric conversion element, a solid photoelectric conversion element provided with a hole transport layer has a higher recombination velocity between holes in the hole transport material and electrons on the electrode surface, so the effect obtained by forming a hole blocking layer is obvious.

[0050] The material of the hole blocking layer is not particularly limited and can be appropriately selected according to the intended purpose, as long as the material of the hole blocking layer is a material transparent to visible light and having electron transport properties. Examples of the material of the hole blocking layer include single semiconductors (e.g., silicon and germanium), compound semiconductors (e.g., chalcogenides of metals), and compounds having a perovskite structure.

[0051] Examples of metal chalcogenides include oxides of titanium, tin, zinc, iron, tungsten, zirconium, hafnium, strontium, indium, cerium, yttrium, lanthanum, vanadium, niobium, and tantalum; sulfides of cadmium, zinc, lead, silver, antimony, and bismuth; selenides of cadmium and lead; and tellurides of cadmium. Other examples of compound semiconductors include phosphides of zinc, gallium, indium, and cadmium; gallium arsenide; copper indium selenide; and copper indium sulfide.

[0052] Examples of the compound having a perovskite structure include strontium titanate, calcium titanate, sodium titanate, barium titanate, and potassium niobate.

[0053] Among the examples listed above, oxide semiconductors are preferred, titanium oxide, niobium oxide, magnesium oxide, aluminum oxide, zinc oxide, tungsten oxide, and tin oxide are more preferred, and titanium oxide is more preferred.

[0054] The examples listed above can be used alone or in combination. The materials listed above can be used as a single layer or a laminate. In addition, there is no specific limitation on the crystal structure of any of the semiconductors listed above, and it can be appropriately selected according to the intended purpose. Its crystal structure can be single crystal, polycrystalline or amorphous.

[0055] The film forming method of the hole blocking layer is not specifically limited and can be appropriately selected according to the intended purpose. Examples of the film forming method of the hole blocking layer include a sol-gel method for wet film formation, a hydrolysis method of titanium tetrachloride, and sputtering for dry film formation. Among the examples listed above, sputtering is preferred. When the film forming method of the hole blocking layer is sputtering, the film density can be made sufficiently high and the current loss can be suppressed.

[0056] The film thickness of the hole blocking layer is not particularly limited and can be appropriately selected according to the intended purpose. The film thickness of the hole blocking layer is preferably 5 nm or more but 1 micrometer or less. In the case of forming a film by a wet system, the film thickness is more preferably 500 nm or more but 700 nm or less. In the case of forming a film by a dry system, the film thickness is more preferably 5 nm or more but 30 nm or less.

[0057] Electron Transport Layer

[0058] The electron transport layer is formed to transport electrons generated by the photosensitive compound to the first electrode or the hole blocking layer. Therefore, the electron transport layer is preferably arranged adjacent to the first electrode or the hole blocking layer.

[0059] The structure of the electron transport layer is not specifically limited and can be appropriately selected according to the intended purpose. In at least two photoelectric conversion elements adjacent to each other, the electron transport layer preferably does not extend to each other. When the electron transport layer does not extend to each other, electron diffusion is suppressed to reduce current leakage. Therefore, considering the improvement of light resistance, this structure is advantageous. In addition, the structure of the electron transport layer can be a continuous single layer, or a multilayer of multiple layers laminated.

[0060] The electron transport layer includes an electron transport material, and may further include other materials as necessary.

[0061] The electron transport material is not particularly limited and can be appropriately selected depending on the intended purpose. The electron transport material is preferably a semiconductor material.

[0062] Preferably, the semiconductor material is in the form of particles, and the porous film is formed by bonding the particles together. The photosensitive compound is chemically or physically adsorbed on the surface of the semiconductor particles constituting the porous electron transport layer.

[0063] The semiconductor material is not particularly limited and may be selected from materials known in the art. Examples of the semiconductor material include a single semiconductor, a compound semiconductor, and a compound having a perovskite structure.

[0064] Examples of single semiconductors include silicon and germanium.

[0065] Examples of compound semiconductors include chalcogenides of metals. Specific examples thereof include oxides of titanium, tin, zinc, iron, tungsten, zirconium, hafnium, strontium, indium, cerium, yttrium, lanthanum, vanadium, niobium, and tantalum; sulfides of cadmium, zinc, lead, silver, antimony, and bismuth; selenides of cadmium and lead; and tellurides of cadmium. Other examples of compound semiconductors include phosphides of zinc, gallium, indium, and cadmium; gallium arsenide; copper indium selenide; and copper indium sulfide.

[0066] Examples of the compound having a perovskite structure include strontium titanate, calcium titanate, sodium titanate, barium titanate, and potassium niobate.

[0067] Among the examples listed above, oxide semiconductors are preferred, and titanium oxide, zinc oxide, tin oxide, and niobium oxide are particularly preferred. When the electron transport material of the electron transport layer is titanium oxide, the conduction band is high and a high open circuit voltage can be obtained. In addition, due to the light confinement effect, the refractive index is high and a high short-circuit current can be obtained. In addition, since the dielectric constant is high and the mobility is high, it is advantageous to use titanium oxide, so a high fill factor can be obtained.

[0068] The examples listed above may be used alone or in combination. In addition, there is no particular limitation on the crystal structure of any semiconductor listed above, and it may be appropriately selected according to the intended purpose. Its crystal structure may be single crystal, polycrystalline or amorphous.

[0069] The number average particle diameter of the primary particles of semiconductor material is not specifically limited, and can be appropriately selected according to the intended purpose. Its number average particle diameter is preferably 1nm or more but 100nm or less, more preferably 5nm or more but 50nm or less. In addition, semiconductor materials with a particle diameter larger than the number average particle diameter can be mixed or laminated. Due to scattered incident light, the use of this semiconductor material can improve conversion efficiency. In this case, the number average particle diameter is preferably 50nm or more but 500nm or less.

[0070] The average thickness of the electron transport layer is not specifically limited and can be appropriately selected according to the intended purpose. The average thickness of the electron transport layer is preferably 50 nm or more but 100 microns or less, more preferably 100 nm or more but 50 microns or less, and even more preferably 120 nm or more but 10 microns or less. When the average thickness of the electron transport layer is within a preferred range, the amount of the photosensitive compound per unit projected area can be fully ensured, a high light capture rate can be maintained, the diffusion length of the injected electrons is not easily increased, and the loss due to charge recombination can be maintained at a low level. Therefore, an electron transport layer having an average thickness within a preferred range is advantageous.

[0071] The method for manufacturing the electron transport layer is not particularly limited and can be appropriately selected according to the intended purpose. Examples of its production method include a method of forming a thin film in a vacuum, such as sputtering; and a wet film forming method. Among the examples listed above, the wet film forming method is preferred in consideration of production cost, and a method of preparing a paste in which a powder or sol of a semiconductor material is dispersed and applying the paste to the first electrode used as an electron collecting electrode substrate or a hole blocking layer is preferred.

[0072] The wet film-forming method is not particularly limited and may be appropriately selected depending on the intended purpose. Examples of the wet film-forming method include dip coating, spray coating, wire bar coating, spin coating, roll coating, blade coating, and gravure coating.

[0073] As the wet printing method, for example, various methods such as relief printing, offset printing, gravure printing, intaglio printing, rubber plate printing, screen printing can be used.

[0074] Examples of methods for producing a dispersion of a semiconductor material include a method in which a semiconductor material is mechanically pulverized using a grinding device known in the art. According to the above method, a specific semiconductor material alone or a mixture of a semiconductor material and a resin is dispersed in water or a solvent to produce a dispersion of a semiconductor material.

[0075] Examples of resins include polymers or copolymers of vinyl compounds (e.g., styrene, vinyl acetate, acrylates, and methacrylates), silicone resins, phenoxy resins, polysulfone resins, polyvinyl butyral resins, polyvinyl formal resins, polyester resins, cellulose ester resins, cellulose ether resins, polyurethane resins, phenolic resins, epoxy resins, polycarbonate resins, polyarylate resins, polyamide resins, and polyimide resins. The examples listed above may be used alone or in combination.

[0076] Examples of the solvent include water, alcohol solvents, ketone solvents, ester solvents, ether solvents, amide solvents, halogenated hydrocarbon solvents, and hydrocarbon solvents.

[0077] Examples of the alcohol solvent include methanol, ethanol, isopropanol, and α-terpineol.

[0078] Examples of the ketone solvent include acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0079] Examples of the ester solvent include ethyl formate, ethyl acetate, and n-butyl acetate.

[0080] Examples of the ether solvent include diethyl ether, dimethoxyethane, tetrahydrofuran, dioxolane and dioxane.

[0081] Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.

[0082] Examples of the halogenated hydrocarbon solvent include dichloromethane, chloroform, bromoform, iodomethane, dichloroethane, trichloroethane, trichloroethylene, chlorobenzene, o-dichlorobenzene, fluorobenzene, bromobenzene, iodobenzene and 1-chloronaphthalene.

[0083] Examples of the hydrocarbon solvent include n-pentane, n-hexane, n-octane, 1,5-hexadiene, cyclohexane, methylcyclohexane, cyclohexadiene, benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, and cumene.

[0084] The examples listed above may be used alone or in combination.

[0085] In order to prevent re-aggregation of particles, an acid, a surfactant, or a chelating agent may be added to a dispersion liquid containing a semiconductor material or a paste containing a semiconductor material obtained by a sol-gel method.

[0086] Examples of the acid include hydrochloric acid, nitric acid, and acetic acid.

[0087] Examples of the surfactant include polyoxyethylene octylphenyl ether.

[0088] Examples of the chelating agent include acetylacetone, 2-aminoethanol and ethylenediamine.

[0089] Furthermore, it is also effective to add a thickener for the purpose of improving film-forming ability.

[0090] Examples of thickeners include polyethylene glycol, polyvinyl alcohol and ethylcellulose.

[0091] After applying the semiconductor material, the semiconductor material may be fired, microwave or electron beam irradiated, or laser beam irradiated to make the particles of the semiconductor material electrically contact each other to improve film strength or adhesion to the substrate. The above-listed methods may be performed individually or in combination.

[0092] In the case of firing an electron transport layer formed of a semiconductor material, the firing temperature is not specifically limited and can be appropriately selected according to the intended purpose. Since the resistance of the substrate may become too high or the material may melt when the temperature is too high, the firing temperature is preferably 30 degrees Celsius or higher but 700 degrees Celsius or lower, and more preferably 100 degrees Celsius or higher but 600 degrees Celsius or lower. In addition, the firing duration is not specifically limited and can be appropriately selected according to the intended purpose. The firing duration is preferably 10 minutes or longer but 10 hours or shorter.

[0093] In the case of irradiating an electron transport layer formed of a semiconductor material with microwaves, the irradiation duration is not particularly limited and can be appropriately selected according to the intended purpose. The irradiation duration is preferably 1 hour or less. In this case, irradiation can be performed from the side where the electron transport layer is formed or from the side where the electron transport layer is not formed.

[0094] After firing the electron transport layer formed of the semiconductor material, for example, chemical plating using a titanium tetrachloride aqueous solution or a mixed solution with an organic solvent or electrochemical plating using a titanium trichloride aqueous solution may be performed in order to enhance electron injection efficiency from the photosensitive compound described below to the semiconductor material.

[0095] The film obtained by sintering a semiconductor material with a particle size of tens of nanometers can form a porous structure. This nanoporous structure has a very high surface area, and the surface area can be represented by a roughness factor. The roughness factor is a numerical value representing the actual area of ​​the inner side of the hole relative to the area of ​​the semiconductor particles applied to the first substrate. Therefore, the larger the value of the roughness factor, the more preferred. Considering the relationship with the average thickness of the electron transport layer, the roughness factor is preferably 20 or more.

[0096] 《Photosensitive compounds》

[0097] In order to further improve the output or photoelectric conversion efficiency, a photosensitive compound is adsorbed on the surface of the semiconductor material constituting the electron transport layer.

[0098] The photosensitizing compound is not particularly limited and may be appropriately selected depending on the intended purpose as long as the photosensitizing compound is a compound that is photoexcited by excitation light emitted to the photoelectric conversion element. Examples of the photosensitizing compound include the following compounds known in the art.

[0099] Specific examples thereof include metal complex compounds disclosed in J. Phys. Chem. C, 7224, Vol. 111 (2007), coumarin compounds, polyene compounds disclosed in Chem. Commun., 4887 (2007), indole compounds disclosed in J. Am. Chem. Soc., 12218, Vol. 126 (2004), Chem. Commun., 3036 (2003), and Angew. Chem. Int. Ed., 1923, Vol. 47 (2008). Thiophene compounds disclosed in J. Am. Chem. Soc., 16701, Vol. 128 (2006), and J. Am. Chem. Soc., 14256, Vol. 128 (2006), J. Phys. Chem., 2342, Vol. 91 (1987), J. Phys. Chem. B, 6272, Vol. 97 (1993), Electroanal. Chem., 31, Vol. 537 (2002), J. Porphyrins Cyanine dyes, merocyanine dyes, 9-arylxanthene compounds, triarylmethane compounds, phthalocyanine compounds, and porphyrin compounds disclosed in Phthalocyanines, 230, Vol. 3 (1999), Angew. Chem. Int. Ed., 373, Vol. 46 (2007), and Langmuir, 5436, Vol. 24 (2008).

[0100] Among the examples listed above, metal complex compounds, coumarin compounds, polyene compounds, indoline compounds and thiophene compounds are preferred. Compounds represented by the following structural formulas (1), (2) and (3) can be purchased from Mitsubishi Paper Mills Ltd., and compounds represented by the following general formula (3) are preferred. The photosensitive compounds listed above can be used alone or in combination.

[0101] [Chemical structure 1]

[0102]

[0103] [Chemical Structure 2]

[0104]

[0105] [Chemical Structure 3]

[0106]

[0107] [Chemical Structure 4]

[0108]

[0109] (In the above formula, X1 and X2 are each an oxygen atom, a sulfur atom and a selenium atom; R1 is a methine group which may have a substituent, wherein specific examples of the substituent include aryl groups (e.g., phenyl and naphthyl) and heterocyclic rings (e.g., thienyl and furyl); R2 is an alkyl group, an aryl group or a heterocyclic group which may have a substituent, wherein examples of the alkyl group include: methyl, ethyl, 2-propyl and 2-ethylhexyl, and examples of the aryl group and the heterocyclic group include the groups listed above; R3 is an acid group such as carboxylic acid, sulfonic acid, phosphonic acid, boric acid and phenols; and Z1 and Z2 are each a substituent for forming a ring structure, wherein examples of Z1 include condensed hydrocarbon-based compounds (e.g., benzene ring and naphthalene ring) and heterocyclic rings (e.g., thiophene ring and furan ring), all of which may have a substituent, specific examples of which include the alkyl groups and alkoxy groups (e.g., methoxy, ethoxy and 2-isopropoxy) listed above, and examples of Z2 include the following (A-1) to (A-22).)

[0110] [Chemical Structure 5]

[0111]

[0112] Specific examples of the photosensitizing compound represented by the general formula (3) include the following (B-1) to (B-28). However, the photosensitizing compound is not limited to the following examples.

[0113] [Chemical Structure 6]

[0114]

[0115]

[0116]

[0117] As a method for adsorbing a photosensitive compound on the surface of a semiconductor material of an electron transport layer, a method of immersing an electron transport layer including a semiconductor material in a solution or dispersion of a photosensitive compound can be used, or a method of applying a solution or dispersion of a photosensitive compound to an electron transport layer to adsorb the photosensitive compound can be used. In the case of a method in which an electron transport layer formed by a semiconductor material is immersed in a solution or dispersion of a photosensitive compound, an immersion method, a dipping method, a roller method, or an air knife method can be used. In the case of a method in which a solution or dispersion of a photosensitive compound is applied to an electron transport layer so that the photosensitive compound is adsorbed on the electron transport layer, wire rod coating, slide hopper coating, extrusion coating, curtain coating, spin coating, or spray coating can be used. In addition, carbon dioxide or the like can be used to adsorb the photosensitive compound on the electron transport layer in a supercritical fluid.

[0118] When the photosensitive compound is adsorbed on the semiconductor material, a condensing agent may be used in combination.

[0119] The condensation agent may be a reagent that exhibits a catalytic function of physically or chemically bonding the photosensitive compound to the surface of the semiconductor material, or a reagent that exhibits a stoichiometric function of favorably shifting the chemical equilibrium. In addition, a thiol or hydroxy compound may be added as a condensation aid.

[0120] Examples of the solvent in which the photosensitive compound is dissolved or dispersed include water, alcohol solvents, ketone solvents, ester solvents, ether solvents, amide solvents, halogenated hydrocarbon solvents, and hydrocarbon solvents.

[0121] Examples of the alcohol solvent include methanol, ethanol, and isopropanol.

[0122] Examples of the ketone solvent include acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0123] Examples of the ester solvent include ethyl formate, ethyl acetate, and n-butyl acetate.

[0124] Examples of the ether solvent include diethyl ether, dimethoxyethane, tetrahydrofuran, dioxolane and dioxane.

[0125] Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.

[0126] Examples of the halogenated hydrocarbon solvent include dichloromethane, chloroform, bromoform, iodomethane, dichloroethane, trichloroethane, trichloroethylene, chlorobenzene, o-dichlorobenzene, fluorobenzene, bromobenzene, iodobenzene and 1-chloronaphthalene.

[0127] Examples of the hydrocarbon solvent include n-pentane, n-hexane, n-octane, 1,5-hexadiene, cyclohexane, methylcyclohexane, cyclohexadiene, benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene and cumene.

[0128] The examples listed above may be used alone or in combination.

[0129] Since there is a photosensitive compound that can function more effectively when preventing aggregation between compounds, an aggregate dissociating agent may be used in combination depending on the kind of the photosensitive compound used.

[0130] The aggregate dissociating agent is not particularly limited and can be appropriately selected according to the dye used. The aggregate dissociating agent is preferably a steroid compound (eg, cholic acid and chenodeoxycholic acid), a long-chain alkyl carboxylic acid, or a long-chain alkyl phosphonic acid.

[0131] The amount of the aggregate dissociating agent is preferably 0.01 parts by mass or more but 500 parts by mass or less, more preferably 0.1 parts by mass or more but 100 parts by mass or less, relative to 1 part by mass of the photosensitive compound.

[0132] The temperature when the photosensitive compound alone or the combination of the photosensitive compound and the aggregate dissociation agent is adsorbed on the surface of the semiconductor material constituting the electron transport layer is preferably -50 degrees Celsius or higher but 200 degrees Celsius or lower. The adsorption duration is preferably 5 seconds or longer but 1,000 hours or shorter, more preferably 10 seconds or longer but 500 hours or shorter, and even more preferably 1 minute or longer but 150 hours or shorter. The adsorption process is preferably carried out in the dark. In addition, the adsorption process can be carried out under standing or stirring.

[0133] The method of stirring is not particularly limited and may be appropriately selected depending on the intended purpose. Examples of the method include methods using a stirrer, a ball mill, a paint conditioner, a sand mill, an attritor, a disperser, and an ultrasonic disperser.

[0134] Hole transport layer

[0135] As the hole transport layer, any material known in the art can be used as long as the hole transport layer has the function of transporting holes. Examples of materials include electrolyte solutions obtained by dissolving redox pairs, gel electrolytes of liquid impregnated polymer matrices obtained by dissolving redox pairs in organic solvents, molten salts including redox pairs, solid electrolytes, inorganic hole transport materials, and organic hole transport materials. In the examples listed above, electrolyte solutions or gel electrolytes can be used, but solid electrolytes are preferred, and organic hole transport materials are more preferred.

[0136] The hole transport layer includes a basic compound represented by the following general formula (1) or general formula (2).

[0137] [Chemical Structure 7]

[0138]

[0139] (In the above formula, R1 and R2 are each independently an alkyl group or an aromatic hydrocarbon group, wherein R1 and R2 may be the same group or different groups, or R1 and R2 may be combined together to form a heterocyclic group including a nitrogen atom.)

[0140] [Chemical structure 8]

[0141]

[0142] (In the above formula, R1 and R2 are each independently an alkyl group or an aromatic hydrocarbon group, wherein R1 and R2 may be the same group or different groups, or R1 and R2 may be combined together to form a heterocyclic group including a nitrogen atom.)

[0143] The hole transport layer preferably contains a basic compound represented by the general formula (1) or (2). The hole transport layer containing the basic compound represented by the general formula (1) or (2) is advantageous in improving the output stability of the photoelectric conversion element, particularly in reducing the fluctuation of the output characteristics of low-light illumination light and stabilizing power generation.

[0144] Specific exemplary compounds of the basic compound represented by the general formula (1) or the general formula (2) will be presented below, but the basic compound used in the present disclosure is not limited to the following examples.

[0145] [Chemical Structure 9]

[0146]

[0147]

[0148] The amount of the basic compound represented by the general formula (1) or (2) in the hole transport layer is preferably 1 part by mass or more but 50 parts by mass or less, and more preferably 10 parts by mass or more but 30 parts by mass or less, relative to 100 parts by mass of the hole transport material. When the amount of the basic compound is within the above preferred range, a high open circuit voltage can be maintained even after long-term use in various environments, a high output can be obtained, and high stability and durability can be obtained.

[0149] The hole transport layer includes a hole transport material or a p-type semiconductor material to obtain the function of transporting holes. As the hole transport material or the p-type semiconductor material, any organic hole transport compound known in the art can be used. Specific examples of the hole transport material or the p-type semiconductor material include Oxadiazole compounds, triphenylmethane compounds, pyrazoline compounds, hydrazone compounds, tetraarylbenzidine compounds, stilbene compounds and spiro compounds.

[0150] Among the examples listed above, spiro compounds are more preferred.

[0151] As the spiro compound, a compound represented by the following general formula (4) is preferred.

[0152] [Chemical Structure 10]

[0153]

[0154] (In the above formula, R9 to R12 are each a substituted amino group, such as dimethylamino, diphenylamino and naphthyl-4-trimethyl.)

[0155] Specific examples of the spiro compound include the following (D-1) to (D-22), but the spiro compound is not limited to the following examples.

[0156] [Chemical Structure 11]

[0157]

[0158]

[0159]

[0160] In addition to the spiro compounds listed above having high hole mobility, two benzidine skeletons are also spirally bonded to form electron clouds, which are close to spherical in shape, and the jumping conductivity between molecules is excellent. Therefore, spiro compounds show excellent photoelectric conversion properties. In addition, due to the high solubility of spiro compounds, spiro compounds are dissolved in a variety of organic solvents. Since spiro compounds are amorphous (irregularly shaped compounds without crystalline structures), spiro compounds tend to be densely filled in porous electron transport layers. In addition, since spiro compounds do not absorb light of 450nm or more, light absorption of photosensitive compounds can be effectively carried out, therefore, spiro compounds are particularly preferably used in solid dye-sensitized solar cells.

[0161] In addition to the hole transport material or the basic compound, an oxidant is preferably added to the hole transport layer. The addition of the oxidant can improve conductivity and enhance durability or stability of output properties.

[0162] Examples of oxidizing agents include tris(4-bromophenyl)ammoniumyl hexachloroantimonate, silver hexafluoroantimonate, nitrosoborate tetrafluoroborate, (nitrosonium), silver nitrate and metal complexes. Among the examples listed above, metal complexes are more preferred. It is advantageous to use metal complexes as oxidants because metal complexes have high solubility in organic solvents and a large amount of oxidants can be added.

[0163] Metal complexes are composed of metal cations, ligands and anions.

[0164] Examples of metal cations include cations of chromium, manganese, iron, cobalt, nickel, copper, molybdenum, ruthenium, rhodium, palladium, silver, tungsten, rhenium, osmium, iridium, gold and platinum. In the examples listed above, cations of cobalt, iron, nickel and copper are preferred, and trivalent cobalt complexes are more preferred. The ligand preferably includes a ligand of a 5-membered and / or 6-membered heterocycle having at least one nitrogen atom, wherein the ligand may include a substituent. Specific examples of the ligand are listed below, but the ligand is not limited to the following examples.

[0165] [Chemical Structure 12]

[0166]

[0167]

[0168] Examples of anions include hydrogen ions (H - ), fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ), hydroxide ion (OH - ), cyanide ion (CN - ), nitrate ion (NO3 - ), nitrite ion (NO2 - ), hypochlorite ion (ClO - ), chlorite ion (ClO2 - ), chlorate ion (ClO3 - ), perchlorate ion (ClO4 - ), permanganate ion (MnO4 - ), acetate ion (CH3COO - ), bicarbonate ion (HCO3 - ), dihydrogen phosphate ion (H2PO4 - ), hydrogen sulfate ion (HSO4 - ), hydrogen sulfide ion (HS - ), thiocyanate ion (SCN - ), tetrafluoroborate ion (BF4 - ), hexafluorophosphate ion (PF6 -), tetracyanoborate ion (B(CN)4 - ), dicyanamide ion (N(CN)2 - ), p-toluenesulfonate ion (TsO - ), trifluoromethanesulfonate ion (CF3SO2 - ), bis(trifluoromethylsulfonyl)amide ion (N(SO2CF3) 2- ), tetrahydroxyaluminate ion ([Al(OH)4] - or [Al(OH)4(H2O)2] - ), silver(I) cyanide ion ([Ag(CN)2] - ), tetrahydrochromate(III) ion ([Cr(OH)4] - ), tetrachloroaurate(III) ion ([AuCl4] - ), oxygen ions (O 2- ), sulfide ion (S 2- ), peroxide ion (O2 2- ), sulfate ion (SO4 2- ), sulfite ion (SO3 2- ), thiosulfate (S2O3 2- ), carbonate ions (CO3 2- ), chromate ion (CrO4 2- ), dichromate ion (Cr2O7 2- ), monohydrogen phosphate ion (HPO4 2- ), tetrahydroxyzincinate (II) ion ([Zn(OH)4] 2- ), tetracyanozincate (II) ion ([Zn(CN)4] 2- ), tetrachlorocuprate(II) ion ([CuCl4] 2- ), phosphate ion (PO4 3- ), hexacyanoferrate (III) ion ([Fe(CN)6] 3- ), silver(I)bis(thiosulfate) ion ([Ag(S2O3)2] 3- ), and hexacyanoferrate (II) ions ([Fe(CN)6] 4- ). Among the examples listed above, tetrafluoroborate ion, hexafluorophosphate ion, tetracyanoborate ion, bis(trifluoromethylsulfonyl)amide ion and perchlorate ion are preferred.

[0169] Among the above metal complexes, trivalent cobalt complexes represented by the following structural formulae (4) and (5) are particularly preferred. Use of a trivalent cobalt complex as the metal complex is advantageous because a decrease in output under light of low illuminance before and after exposure to light of high illuminance can be prevented.

[0170] [Chemical structure 13].

[0171]

[0172] [Chemical Structure 14]

[0173]

[0174] [Chemical Structure 15]

[0175]

[0176] The examples listed above may be used alone or in combination.

[0177] The content of the oxidant is preferably 0.5 parts by mass or more but 30 parts by mass or less, and more preferably 1 part by mass or more but 15 parts by mass, relative to 100 parts by mass of the hole transport material. It is not necessary to oxidize the entire hole transport material by adding the oxidant, and therefore its addition is effective as long as at least a part of the hole transport material is oxidized.

[0178] In addition, the hole transport layer preferably further contains an alkali metal salt. The hole transport layer containing the alkali metal salt can improve output, and further, the hole transport layer can improve light irradiation resistance or high temperature storage resistance.

[0179] Examples of alkali metal salts include lithium salts such as lithium chloride, lithium bromide, lithium iodide, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium diisopropylimide, lithium acetate, lithium tetrafluoroborate, lithium pentafluorophosphate, and lithium tetracyanoborate; sodium salts such as sodium chloride, sodium bromide, sodium iodide, sodium perchlorate, sodium bis(trifluoromethanesulfonyl)imide, sodium acetate, sodium tetrafluoroborate, sodium pentafluorophosphate, and sodium tetracyanoborate; and potassium salts such as potassium chloride, potassium bromide, potassium iodide, and potassium perchlorate. Among the examples listed above, lithium bis(trifluoromethanesulfonyl)imide and lithium diisopropylimide are preferred.

[0180] The amount of the alkali metal salt is preferably 1 part by mass or more but 50 parts by mass or less, more preferably 5 parts by mass or more but 30 parts by mass or less, relative to 100 parts by mass of the hole transport material.

[0181] The hole transport layer may have a single layer structure formed by a single material, or a laminated structure including multiple compounds. In the case where the hole transport layer has a laminated structure, it is preferred that a polymer material is used for a layer of the hole transport layer disposed near the second electrode. It is advantageous to use a polymer material having excellent film-forming properties because the surface of the porous electron transport layer can be made smoother and the photoelectric conversion properties can be improved. In addition, since the polymer material is not easy to penetrate into the porous electron transport layer, it is desirable to cover the surface of the porous electron transport layer, and the effect of preventing short circuits when the electrodes are set can be obtained.

[0182] Examples of the polymer material used for the hole transport layer include hole transport polymer materials known in the art.

[0183] Examples of the hole transport polymer material include polythiophene compounds, polyphenylenevinylene compounds, polyfluorene compounds, polyfluorene compounds, polyphenylene compounds, polyarylamine compounds, and polythiadiazole compounds.

[0184] Examples of the polythiophene compound include poly(3-n-hexylthiophene), poly(3-n-octyloxythiophene), poly(9,9′-dioctyl-fluorene-co-bithiophene), poly(3,3″′-dodecyl-quaterthiophene), poly(3,6-dioctylthieno[3,2-b]thiophene), poly(2,5-bis(3-decylthiophen-2-yl)thieno[3,2-b]thiophene), poly(3,4-didecylthiophene-co-thieno[3,2-b]thiophene), poly(3,6-dioctylthieno[3,2-b]thiophene-co-thieno[3,2-b]thiophene), Poly(3,6-dioctylthieno[3,2-b]thiophene-co-thiophene and poly(3,6-dioctylthieno[3,2-b]thiophene-co-bithiophene). Examples of the polyphenylene vinylene compound include poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3,7-dimethyloctyloxy)-1,4-phenylene vinylene], and poly[(2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene)-co-(4,4'-biphenylene-vinylene)].

[0185] Examples of the polyfluorene compounds include poly(9,9′-dodecylfluorenyl-2,7-diyl), poly[(9,9-dioctyl-2,7-divinylenefluorene)-alt-co-(9,10-anthracene)], poly[(9,9-dioctyl-2,7-divinylenefluorene)-alt-co-(4,4′-biphenylene)], poly[(9,9-dioctyl-2,7-divinylenefluorene)-alt-co-(2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene)], and poly[(9,9-dioctyl-2,7-diyl)-co-(1,4-(2,5-dihexyloxy)benzene)].

[0186] Examples of the polyphenylene compound include poly[2,5-dioctyloxy-1,4-phenylene] and poly[2,5-di(2-ethylhexyloxy-1,4-phenylene].

[0187] Examples of the polyarylamine compound include poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-co-(N,N'-diphenyl)-N,N'-di(p-hexylphenyl)-1,4-diaminobenzene], poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-co-(N,N'-bis(4-octyloxyphenyl)benzidine-N,N'-(1,4-diphenylene)], poly[(N,N'-bis(4-octyloxyphenyl)benzidine-N,N'-(1,4-diphenylene)] , poly[(N,N'-bis(4-(2-ethylhexyloxy)phenyl)benzidine-N,N'-(1,4-diphenylene)], poly[phenylimino-1,4-phenylenevinylene-2,5-dioctyloxy-1,4-phenylenevinylene-1,4-phenylene], poly[p-tolylimino-1,4-phenylenevinylene-2,5-di(2-ethylhexyloxy)-1,4-phenylenevinylene-1,4-phenylene], and poly[4-(2-ethylhexyloxy)phenylimino-1,4-biphenylene].

[0188] Examples of the polythiadiazole compound include poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-co-(1,4-benzo(2,1′,3)thiadiazole] and poly(3,4-didecylthiophene-co-(1,4-benzo(2,1′,3)thiadiazole).

[0189] Among the examples listed above, polythiophene compounds and polyarylamine compounds are preferred in view of carrier mobility and ionization potential.

[0190] The average thickness of the hole transport layer is not particularly limited and can be appropriately selected according to the intended purpose. The hole transport layer preferably has a structure in which the hole transport layer penetrates the holes of the porous electron transport layer. The average thickness of the hole transport layer on the electron transport layer is preferably 0.01 micrometers or more but 20 micrometers or less, more preferably 0.1 micrometers or more but 10 micrometers or less, and even preferably 0.2 micrometers or more but 2 micrometers or less.

[0191] The hole transport layer can be directly formed on the electron transport layer adsorbed with the photosensitive compound. The production method of the hole transport layer is not specifically limited and can be appropriately selected according to the intended purpose. Examples of its production method include methods of forming a thin film in a vacuum, such as vapor deposition; and wet film forming methods. Among the examples listed above, considering the production cost, the wet film forming method is particularly preferred. It is preferred to apply the hole transport layer to the electron transport layer.

[0192] In the case of wet film forming method, coating method is not specifically limited and can be carried out according to any method known in the art. Examples of coating methods include dip coating, spray coating, wire rod coating, spin coating, roller coating, blade coating and gravure coating. As wet printing method, various methods can be used, such as relief printing, offset printing, gravure printing, intaglio printing, rubber plate printing, screen printing.

[0193] In addition, film can be formed in a supercritical fluid or subcritical fluid at a temperature and pressure lower than a critical point. Supercritical fluid is not specifically limited, and can be appropriately selected according to the intended purpose, as long as the supercritical fluid is a fluid that exists in the form of a non-condensable high-pressure fluid in a temperature and pressure region exceeding a limit value (critical point), wherein gas and liquid can coexist without being compressed and condensed, and is a fluid in a state equal to or higher than a critical temperature and equal to or higher than a critical pressure. Supercritical fluid is preferably a supercritical fluid with a low critical temperature.

[0194] Examples of the supercritical fluid include carbon monoxide, carbon dioxide, ammonia, nitrogen, water, alcohol solvents, hydrocarbon solvents, halogen solvents, and ether solvents.

[0195] Examples of the alcohol solvent include methanol, ethanol and n-butanol.

[0196] Examples of hydrocarbon solvents include ethane, propane, 2,3-dimethylbutane, benzene, and toluene. Examples of halogen solvents include dichloromethane and chlorotrifluoromethane.

[0197] Examples of the ether solvent include dimethyl ether.

[0198] The examples listed above may be used alone or in combination.

[0199] Among the examples listed above, carbon dioxide is preferable because carbon dioxide has a critical pressure of 7.3 MPa and a critical temperature of 31 degrees Celsius, and thus a supercritical state of carbon dioxide is easily formed and carbon dioxide is inflammable and easy to handle.

[0200] There is no particular limitation on the subcritical fluid and may be appropriately selected depending on the intended purpose as long as the subcritical fluid is a fluid that exists as a high-pressure fluid in a temperature and pressure region near the critical point. Compounds listed as supercritical compounds may also be suitably used as subcritical fluids.

[0201] There is no particular limitation on the critical temperature and critical pressure of the supercritical fluid and may be appropriately selected depending on the intended purpose. The critical temperature is preferably -273 degrees Celsius or higher but 300 degrees Celsius or lower, and more preferably 0 degrees Celsius or higher but 200 degrees Celsius or lower.

[0202] In addition to the supercritical fluid or subcritical fluid, an organic solvent or an entrainer may be used in combination. By adding an organic solvent or an entrainer, solubility in a supercritical fluid can be easily performed.

[0203] The organic solvent is not particularly limited and may be appropriately selected depending on the intended purpose. Examples of the organic solvent include ketone solvents, ester solvents, ether solvents, amide solvents, halogenated hydrocarbon solvents, and hydrocarbon solvents.

[0204] Examples of the ketone solvent include acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0205] Examples of the ester solvent include ethyl formate, ethyl acetate, and n-butyl acetate.

[0206] Examples of the ether solvent include diisopropyl ether, dimethoxyethane, tetrahydrofuran, dioxolane and dioxane.

[0207] Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.

[0208] Examples of the halogenated hydrocarbon solvent include dichloromethane, chloroform, bromoform, iodomethane, dichloroethane, trichloroethane, trichloroethylene, chlorobenzene, o-dichlorobenzene, fluorobenzene, bromobenzene, iodobenzene and 1-chloronaphthalene.

[0209] Examples of the hydrocarbon solvent include n-pentane, n-hexane, n-octane, 1,5-hexadiene, cyclohexane, methylcyclohexane, cyclohexadiene, benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, and cumene.

[0210] The examples listed above may be used alone or in combination.

[0211] In addition, after laminating the hole transport material on the electron transport layer adsorbed with the photosensitive compound, pressing may be performed. Since the hole transport material is more closely attached to the electron transport layer as a porous electrode by performing pressing, efficiency may be improved.

[0212] The pressing method is not particularly limited and can be appropriately selected depending on the intended purpose. Examples of the method include compression molding using a plate such as an IR press; and roll pressing using a roll.

[0213] The pressure is preferably 10kgf / cm 2 or more, more preferably 30kgf / cm 2 or above.

[0214] The duration of pressing is not specifically limited and can be appropriately selected according to the intended purpose. The duration is preferably 1 hour or less. In addition, heat can be applied during pressing. During pressing, a release agent can be provided between the press and the electrode.

[0215] Examples of the release agent include fluorine resins such as polytetrafluoroethylene, polychlorotrifluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymers, perfluoroalkoxy fluorocarbon resins, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymers, ethylene-chlorotrifluoroethylene copolymers, and polyvinyl fluoride. The examples listed above may be used alone or in combination.

[0216] After performing the pressing but before disposing the second electrode, a metal oxide may be disposed between the hole transport material and the second electrode.

[0217] Examples of metal oxides include molybdenum oxide, tungsten oxide, vanadium oxide and nickel oxide. The examples listed above can be used alone or in combination. Among the examples listed above, molybdenum oxide is preferred.

[0218] The method of disposing the metal oxide on the hole transport layer is not particularly limited and can be appropriately selected depending on the intended purpose. Examples of the method include a method of forming a thin film in a vacuum, such as sputtering and vacuum vapor deposition; and a wet film-forming method.

[0219] As a wet film forming method, it is preferred to prepare a paste of a powder or sol dispersed with a metal oxide, and apply the paste to a method on a hole transport layer. In the case of using a wet film forming method, the coating method is not specifically limited, and can be carried out according to any method known in the art. The example of the coating method includes dip coating, spray coating, wire rod coating, spin coating, roller coating, blade coating and gravure coating. In addition, as a wet printing method, various methods can be used, such as relief printing, offset printing, gravure printing (gravure printing), gravure printing (intaglio printing), rubber plate printing, screen printing.

[0220] The average thickness of the applied metal oxide is preferably 0.1 nm or more but 50 nm or less, more preferably 1 nm or more but 10 nm or less.

[0221] The Second Electrode

[0222] The second electrode may be formed on the hole transport layer or on the metal oxide of the hole transport layer. In addition, as the second electrode, the same electrode as the first electrode may be used. In the case where the strength of the second electrode can be sufficiently ensured, a support is not necessarily required.

[0223] Examples of the material of the second electrode include metals, carbon compounds, conductive metal oxides, and conductive polymers.

[0224] Examples of metals include platinum, gold, silver, copper, and aluminum.

[0225] Examples of carbon compounds include graphite, fullerene, carbon nanotube, and graphene.

[0226] Examples of the conductive metal oxide include ITO, FTO, and ATO.

[0227] Examples of conductive polymers include polythiophene and polyaniline.

[0228] The examples listed above may be used alone or in combination.

[0229] The second electrode may be formed on the hole transport layer by an appropriate method such as coating, lamination, vapor deposition, CVD, and bonding, depending on the material of the second electrode used or the hole transport layer used.

[0230] In the photoelectric conversion element, at least one of the first electrode and the second electrode is preferably substantially transparent. Preferably, the first electrode side is transparent, and the incident light enters the photoelectric conversion element from the first electrode side. In this case, it is preferred to use a material that reflects light on the second electrode side. As the material that reflects light, it is preferred to use glass or plastic on which a metal or conductive oxide is deposited by vapor deposition, or a metal film. In addition, it is also effective to set an anti-reflection layer on the side where the incident light enters.

[0231] Second Baseboard

[0232] The second substrate is not specifically limited and can be selected from substrates known in the art. Examples of the second substrate include substrates of glass, plastic film and ceramic. Concavo-convex portions can be formed at the contact area of ​​the second substrate and the sealing member to increase the adhesion between the second substrate and the sealing member.

[0233] The formation method of the concavoconvex portion is not particularly limited and can be appropriately selected depending on the intended purpose. Examples of the formation method include sand blasting, water blasting, polishing with sandpaper, chemical etching, and laser processing.

[0234] As a method of increasing the adhesion between the second substrate and the sealing member, for example, organic matter on the surface thereof can be removed or the hydrophilicity of the surface thereof can be increased. The method of removing organic matter on the surface of the second substrate is not specifically limited and can be appropriately selected according to the intended purpose. Examples of the method include UV ozone washing and oxygen plasma treatment.

[0235] Sealing components

[0236] Examples of the sealing resin include acrylic resin and epoxy resin.

[0237] As the cured product of the acrylic resin, any material known in the art may be used as long as the cured product of the acrylic resin is a product obtained by curing a monomer or an oligomer containing an acryl group in its molecule.

[0238] As the cured product of the epoxy resin, any material known in the art may be used as long as the cured product of the epoxy resin is a product obtained by curing a monomer or an oligomer containing an epoxy group in its molecule.

[0239] Examples of epoxy resins include water-dispersible epoxy resins, non-solvent epoxy resins, solid epoxy resins, heat-cured epoxy resins, epoxy resins mixed with curing agents, and ultraviolet curing epoxy resins. In the examples listed above, heat-cured epoxy resins and ultraviolet curing epoxy resins are preferred, and ultraviolet curing epoxy resins are more preferred. Note that even ultraviolet curing resins can be heated, and even after the epoxy resin is cured by ultraviolet irradiation, it is preferably heated.

[0240] Examples of epoxy resins include bisphenol A epoxy resins, bisphenol F epoxy resins, novolac epoxy resins, alicyclic epoxy resins, long-chain aliphatic epoxy resins, glycidylamine epoxy resins, glycidylether epoxy resins, and glycidylester epoxy resins. The examples listed above may be used alone or in combination.

[0241] It is preferred to mix a curing agent or various additives with the epoxy resin as necessary.

[0242] The curing agent is classified into amine curing agents, acid anhydride curing agents, polyamine curing agents and other curing agents. The curing agent is appropriately selected according to the intended purpose.

[0243] Examples of the amine curing agent include aliphatic polyamines such as diethylenetriamine and triethylenetetramine; and aromatic polyamines such as methphenylenediamine, diaminodiphenylmethane, and diaminodiphenylsulfone.

[0244] Examples of the acid anhydride curing agent include phthalic anhydride, tetra- or hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnaphthalic anhydride, pyromellitic anhydride, HET anhydride, and dodecenylsuccinic anhydride.

[0245] Examples of other curing agents include imidazoles and polythiols. The examples listed above may be used alone or in combination.

[0246] Examples of additives include fillers, interstitials, polymerization initiators, desiccants (dehumidifiers), curing accelerators, coupling agents, toughening agents, colorants, flame retardant aids, antioxidants, and organic solvents. Among the examples listed above, fillers, interstitials, curing accelerators, polymerization initiators, and desiccants (dehumidifiers) are preferred, and fillers and polymerization initiators are more preferred.

[0247] Fillers not only effectively inhibit the entry of moisture or oxygen, but also have the effect of reducing the exhaust volume during curing or heating, improving mechanical strength, controlling heat transfer rate or fluidity, and fillers are very effective in maintaining stable output under various environments. Specifically, the output properties or durability of the photoelectric conversion element are not simply affected by moisture or oxygen, but also the influence of the exhaust gas generated when curing or heating the sealing member cannot be ignored. Specifically, the exhaust gas generated during heating greatly affects the output properties of the photoelectric conversion element stored in a high temperature environment.

[0248] In this case, the ingress of moisture or oxygen can be suppressed by adding a filler, a gap agent or a desiccant to the sealing member, and thus the amount of the sealing member used can be reduced, thereby obtaining the effect of reducing the exhaust gas. The use of such additives is effective not only during curing, but also when the photoelectric conversion element is stored in a high temperature environment.

[0249] There is no specific limitation on the filler, and any filler known in the art can be used as the filler. For example, it is preferred to use an inorganic filler, such as crystalline or irregular silica, talc, aluminum oxide, aluminum nitrate, calcium silicate and calcium carbonate. The examples listed above can be used alone or in combination. The average primary particle size of the filler is preferably 0.1 micron or more but 10 microns or less, more preferably 1 micron or more but 5 microns or less. When the average primary particle size is within the above-mentioned preferred range, the effect of suppressing the entry of moisture or oxygen can be fully obtained, appropriate viscosity is obtained, adhesion or defoaming properties with the substrate are improved, and it is effective for controlling the width or processability of the sealing portion.

[0250] The amount of the filler is preferably 10 parts by mass or more but 90 parts by mass or less, more preferably 20 parts by mass or more but 70 parts by mass or less, relative to 100 parts by mass of the entire sealing member. When the amount of the filler is within the above range, the effect of inhibiting the entry of moisture or oxygen can be fully obtained, appropriate viscosity can be obtained, and excellent adhesion and workability can be obtained.

[0251] The gap agent is also called a gap control agent or a spacer, and is configured to control the gap of the sealing part. For example, when the sealing member is applied to the first substrate of the first electrode and the second substrate is placed thereon for sealing, since the gap agent is mixed with the epoxy resin, the gap of the sealing part matches the size of the gap agent, and thus the gap of the sealing part can be easily controlled.

[0252] As the interstitial agent, any material known in the art can be used, as long as the interstitial agent is a granular material with uniform particle size and high solvent resistance and heat resistance. The interstitial agent is preferably a material with high affinity for epoxy resin and spherical particle shape. Specific examples of the interstitial agent include glass beads, silica particles and organic resin particles. The examples listed above can be used alone or in combination.

[0253] The particle size of the gap agent can be selected according to the gap of the sealing portion to be set. The particle size is preferably 1 micrometer or more but 100 micrometers or less, and more preferably 5 micrometers or more but 50 micrometers or less.

[0254] The polymerization initiator is a material added to initiate polymerization using heat or light.

[0255] A thermal polymerization initiator is a compound that generates active substances such as free radicals and cations when heated. As a thermal polymerization initiator, specifically, an azo compound such as 2,2'-azobisisobutyronitrile (AIBN) or a peroxide such as benzoyl peroxide (BPO) is used. As a thermal cationic polymerization initiator, a benzenesulfonate or an alkyl sulfonium salt is used. As a photopolymerization initiator, a photocationic polymerization initiator is preferably used for an epoxy resin. When the photocationic polymerization initiator is mixed with an epoxy resin and irradiated with light, the photocationic polymerization initiator decomposes to generate a strong acid, and the acid induces polymerization of the epoxy resin to perform a curing reaction. The photocationic polymerization initiator has the following effects: small volume shrinkage during curing, no oxygen inhibition occurs, and high storage stability.

[0256] Examples of the photocationic polymerization initiator include aromatic diazonium salts, aromatic iodine Onium salts, aromatic sulfonium salts, metallocene compounds and silanol-aluminum complexes.

[0257] In addition, a photoacid generator having a function of generating an acid when irradiated with light may also be used. The photoacid generator is used as an acid that initiates cationic polymerization. Examples of the photoacid generator include Salts, for example, sulfonium salt-based photoacid generators consisting of a cationic portion, an anionic portion and an ionic portion, and ionic iodine salts consisting of a cationic portion and an anionic portion. Salt. The examples listed above may be used alone or in combination.

[0258] The amount of polymerization initiator added can vary depending on the material used. Relative to 100 parts by mass of the entire sealing member, the amount of polymerization initiator is preferably 0.5 parts by mass or more but 10 parts by mass, more preferably 1 part by mass or more but 5 parts by mass or less. The polymerization initiator added in the amount of the above range is effective because curing can be properly performed, the uncured residual amount can be reduced, and excessive degassing can be prevented.

[0259] Desiccant, also called dehumidifier, is a material that has the function of physically or chemically adsorbing or absorbing moisture. By adding desiccant to the sealing member, there is a possibility that moisture resistance is further improved or the influence of degassing may be reduced. Therefore, the use of desiccant is effective.

[0260] The desiccant is preferably a granular material. Examples of desiccant include inorganic water-absorbing materials, such as calcium oxide, barium oxide, magnesium oxide, magnesium sulfate, sodium sulfate, calcium chloride, silica gel, molecular sieves and zeolites. Of the examples listed above, zeolites are preferred because zeolites have a large amount of hygroscopicity. The examples listed above can be used alone or in combination.

[0261] Curing accelerators are also called curing catalysts and are used for the purpose of accelerating the curing speed. Curing accelerators are mainly used for heat-cured epoxy resins.

[0262] Examples of curing accelerators include: tertiary amines or tertiary amine salts, such as 1,8-diazabicyclo (5,4,0)-undec-7-ene (DBU) and 1,5-bicyclo (4,3,0)-non-5-ene (DBN); imidazole curing accelerators, such as 1-cyanoethyl-2-ethyl-4-methylimidazole and 2-ethyl-4-methylimidazole; and phofine or Salts such as triphenylphosphine and tetraphenylboron The examples listed above may be used alone or in combination.

[0263] The coupling agent has the effect of increasing the molecular bonding force. Examples of coupling agents include silane coupling agents. Examples of coupling agents include: silane coupling agents, such as 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl dimethoxysilane, 3-glycidyloxypropyl dimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, N-(2-aminoethyl) 3-aminopropyl methyl dimethoxysilane, N-(2-aminoethyl) 3-aminopropyl methyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-mercaptopropyl trimethoxysilane, vinyl trimethoxysilane, N-(2-(vinylbenzylamino)ethyl) 3-aminopropyl trimethoxysilane hydrochloride and 3-methacryloxypropyl trimethoxysilane. The examples listed above can be used alone or in combination.

[0264] In addition, as sealing member, it is known that commercially available epoxy resin compositions as encapsulants, sealing materials or adhesives, and such products can be used in the present disclosure. Among these products, there are developed and commercially available epoxy resin compositions for solar cells or organic EL elements, and these products are particularly effectively used in the present disclosure. Examples thereof include: TB3118, TB3114, TB3124 and TB3125F (available from ThreeBond); WorldRock5910, WorldRock5920 and WorldRock8723 (available from Kyoritsu Chemical Co., Ltd.); and WB90US (P) (available from MORESCO).

[0265] In the present disclosure, a sealing sheet material may be used.

[0266] The sealing plate material is a material on which an epoxy resin layer is formed in advance. As the plate, glass or film with high gas barrier properties can be used. The plate corresponds to the second substrate of the present disclosure. By bonding the sealing plate material to the substrate and then curing it, a sealing member and a second substrate can be formed at the same time. The use of the sealing plate material is effective because a structure having a void portion can be formed by patterning the epoxy resin layer formed on the plate.

[0267] The formation method of the sealing member is not particularly limited, and the sealing member can be formed according to any method known in the art. For example, any of a variety of methods can be used, such as dispensing, wire rod coating, spin coating, roller coating, scraping, gravure coating, relief printing, offset printing, gravure printing, rubber plate printing and screen printing.

[0268] In addition, a passivation layer may be provided between the sealing member and the second electrode. The passivation layer is not specifically limited and may be appropriately selected according to the intended purpose, as long as the passivation layer is provided in a manner such that the sealing member does not contact the second electrode. As the passivation layer, aluminum oxide, silicon nitride or silicon oxide is preferably used.

[0269] Embodiments for carrying out the present disclosure will be described with reference to the accompanying drawings. In the accompanying drawings, the same numerals are given to the same structural parts, and duplication of description may be avoided by omission.

[0270] <Component Structure>

[0271] Figure 1 Schematic diagram showing an example of a photoelectric conversion element of the disclosure. Figure 1 As shown, the photoelectric conversion element 101 includes a first electrode 2 formed on a first substrate 1. An electron transport layer 4 is formed on the first electrode 2, and a photosensitive compound 5 is adsorbed on the surface of the electron transport material constituting the electron transport layer 4. On the upper part and inside of the electron transport layer 4, a hole transport layer 6 is formed. A second electrode 7 is formed on the hole transport layer 6. On the upper side of the second electrode 7, a second substrate 9 is provided. The second substrate 9 is fixed to the first electrode 2 via a sealing member 8. As shown in FIG. Figure 1 The photoelectric conversion element shown has a gap portion between the second electrode 7 and the second substrate 9. Due to the arrangement of the gap portion, the moisture or oxygen concentration inside the gap portion can be controlled, and the power generation capacity or durability can be improved. In addition, since the second electrode 7 and the second substrate 9 are not in direct contact with each other, it is possible to prevent the second electrode 7 from peeling off or breaking. The oxygen concentration inside the gap portion is not specifically limited and can be freely selected. The oxygen concentration is preferably 0% or more but 21% or less, more preferably 0.05% or more but 10% or less, and even more preferably 0.1% or more but 5% or less.

[0272] Although not shown, each of the first electrode 2 and the second electrode 7 has a path for conducting electricity from each electrode to each electrode output terminal.

[0273] Figure 2 is a schematic diagram illustrating another example of the photoelectric conversion element of the present disclosure. A hole blocking layer 3 is formed between the first substrate 1 and the electron transport layer 4. The formation of the hole blocking layer 3 can prevent the recombination of electrons and holes and is effective for improving the power generation capability. Figure 1 , Figure 2 The photoelectric conversion element shown has a gap between the second electrode 7 and the second substrate 9 .

[0274] Figure 3 is a schematic diagram illustrating another example of the photoelectric conversion element of the present disclosure, and illustrates Figure 2The example of the gap portion of the second electrode 7 being covered by the sealing member 8. For example, the photoelectric conversion element can be formed by applying the sealing member 8 on the entire surface of the second electrode 7 and arranging the second substrate 9 thereon, or by using the above-mentioned sealing plate method. In this case, the gap portion inside the seal can be completely removed, or the gap portion can be partially retained. By covering the substantially entire surface of the second electrode with the sealing member as described above, the peeling or breakage of the second substrate 9 can be reduced, and the mechanical strength of the photoelectric conversion element can be improved.

[0275] Figure 4 1 is a schematic diagram illustrating another example of the photoelectric conversion element of the present disclosure, and illustrates that the sealing member 8 is bonded to the first substrate 1 and the second substrate 9. Since the photoelectric conversion element has the above structure, the adhesion between the sealing member 8 and the substrate is strong, and thus the effect of enhancing the mechanical strength of the photoelectric conversion element can be obtained. In addition, since the close adhesion between the sealing member and the substrate is enhanced, the effect of enhancing the sealing effect of preventing moisture or oxygen from entering can be obtained.

[0276] Figure 5 1 is a schematic diagram illustrating an example of a solar cell module of the present disclosure, and illustrates an example of a solar cell module in which a plurality of photoelectric conversion elements are included and the photoelectric conversion elements are connected in series. Figure 5 In the example of , the through-hole 10 is formed after the hole transport layer 6 is formed, and then the second electrode 7 is formed, so that the second electrode material is introduced into the through-hole 10 and is connected to the first electrode 2b of the adjacent unit. Figure 5 Not shown in the drawings, each of the first electrode 2a and the second electrode 7b has a path for conducting electricity from each electrode to an electrode of an adjacent cell or an output terminal.

[0277] exist Figure 5 In at least two mutually adjacent photoelectric conversion elements in the solar cell module 102, the hole transport layer 6 is connected together without connecting the hole blocking layer 3 together. Therefore, the solar cell module 102 hardly generates leakage current under light of high illuminance, and the photosensitive compound is not easily damaged, so the output reduction of light of low illuminance before or after exposure to light of high illuminance can be suppressed. Therefore, even after exposure to sunlight, the solar cell module 102 can have high power output by using light emitted from indoor light illuminance devices such as LEDs and fluorescent lamps.

[0278] Note that the through portion 10 may pierce the first electrode 2 to reach the first substrate 1. Alternatively, the process may be stopped when the through portion 10 reaches the inside of the first electrode 2 and the through portion 10 may not reach the first substrate 1. In the case where the through portion 10 is in the shape of a hole that penetrates the first electrode 2 and reaches the first substrate 1, if the total opening area of ​​the hole is too large relative to the area of ​​the through portion 10, the resistance value increases as the cross-sectional film area of ​​the first electrode 2 decreases, and thus the photoelectric conversion efficiency may decrease. Therefore, the ratio of the total opening area of ​​the hole to the area of ​​the through portion 10 is preferably 5 / 100 to 60 / 100.

[0279] In addition, examples of methods for forming the through-portion 10 include sandblasting, water jetting, polishing with sandpaper, chemical etching, and laser processing. In the present disclosure, laser processing is preferred because fine pores can be formed without using sand, etching, or resists, and processing can be performed cleanly and with good reproducibility. Another reason for preferring laser processing is that in some cases, at least one or all of the layers listed above can be removed by impact stripping by laser processing when forming the through-portion 10. Therefore, there is no need to set a mask during lamination, and the removal and formation of the fine through-portion 10 can be performed simply and easily at one time.

[0280] Figure 6 is a schematic diagram illustrating an example of a solar cell module of the present disclosure. Figure 5 Differently, the electron transport layer 4 is cut off from the adjacent photoelectric conversion element, and each photoelectric conversion element has an independent layer structure. Figure 6 The electron transport layers 4 in the illustrated solar cell module 102 do not extend to each other, thus reducing current leakage by suppressing electron diffusion and thus improving light resistance.

[0281] Figure 7 1 is a schematic diagram illustrating an example of a solar cell module of the present disclosure, and illustrates an example in which the solar cell module includes a plurality of photoelectric conversion elements connected in series, and a sealing member is provided in a gap portion between celllike beams. Figure 2 In the case where a gap is provided between the second electrode 7 and the second substrate 9, the second electrode 7 can be prevented from peeling off or breaking, but the mechanical strength of the seal may be reduced. Figure 3 In the case where the gap between the second electrode 7 and the second substrate 9 is filled with a sealing member, the mechanical strength of the seal increases, but the peeling of the second electrode 7 may occur. In order to increase power generation, it is effective to increase the area of ​​the solar cell module, but when the solar cell module has a gap portion, a decrease in mechanical strength is inevitable. In this case, Figure 7 As shown, by providing the sealing member like a beam, the peeling or breakage of the second substrate 9 can be prevented, and the mechanical strength of the seal can be enhanced.

[0282] By using in combination with a circuit board configured to control the generated current, the solar cell module of the present invention can be applied to a power supply device. Examples of devices that can use such a power supply device include electronic calculators and watches. In addition, the power supply device including the photoelectric conversion element of the present disclosure can be applied to mobile phones, electronic notepads and electronic paper. In addition, the power supply device including the photoelectric conversion element of the present disclosure can be used as an auxiliary power supply to extend the continuous use period of an electrical appliance loaded with a rechargeable or dry battery.

[0283] Example

[0284] The present disclosure will be described in more detail below by way of examples. The present disclosure should not be construed as being limited to these examples.

[0285] (Example 1)

[0286] <Solar Cell Module Production>

[0287] An indium tin (ITO) film and a niobium tin oxide (NTO) film as a first electrode were sequentially deposited on a glass substrate used as a first substrate by sputtering. Subsequently, a dense layer formed of titanium oxide used as a hole blocking layer was formed by reactive sputtering. Subsequently, a portion of the ITO / NTO and the hole blocking layer formed on the substrate was etched by laser processing so that the interval between adjacent photoelectric conversion elements was 10 micrometers.

[0288] Subsequently, 3 g of titanium oxide (ST-21, available from ISHIHARA SANGYOKAISHA, LTD., Japan), 0.2 g of acetylacetone and 0.3 g of a surfactant (polyoxyethylene octylphenyl ether, available from Wako Pure Chemical Corporation) were bead milled together with 5.5 g of water and 1.0 g of ethanol for 12 hours to obtain a titanium oxide dispersion. To the obtained titanium oxide dispersion, 1.2 g of polyethylene glycol (#20,000, available from Wako Pure Chemical Corporation) was added to produce a paste. The obtained paste was applied to the hole blocking layer in an average thickness of about 1.5 microns. After the applied paste was dried at 60 degrees Celsius, it was fired in air at 550 degrees Celsius for 30 minutes to form a porous electron transport layer.

[0289] The glass substrate on which the electron transport layer had been formed was immersed in a solution obtained by adding acetonitrile / tert-butyl alcohol (volume ratio: 1 / 1) to 120 mg of a photosensitive compound represented by B-5 and 150 mg of chenodeoxycholic acid (obtained from Tokyo Chemical Industry Co., Ltd.), and allowed to stand in the dark for 1 hour to allow the photosensitive compound to be adsorbed on the surface of the electron transport layer.

[0290] Subsequently, 15.0 mg of lithium bis(trifluoromethanesulfonyl)imide (available from KANTOCHEMICAL CO., LTD.) and 40 mg of a basic compound represented by C-12 were added and dissolved in 1 mL of a chlorobenzene solution including 183 mg of a hole transport material represented by D-7 (available from Merck KGaA) to prepare a hole transport layer coating liquid.

[0291] Next, the hole transport layer coating liquid is applied to the electron transport layer on which the photosensitive compound is adsorbed by spin coating, thereby forming a hole transport layer with a thickness of about 500nm. Thereafter, the edge of the glass substrate on which the sealing member is disposed is etched by laser processing, and a through hole for connecting the elements in series is formed by laser processing. In addition, silver is deposited thereon by vacuum vapor deposition to form a second electrode having a thickness of about 100nm. A mask film is formed so that the distance between adjacent photoelectric conversion elements is 200 microns. In addition, it is confirmed that silver is deposited on the inner wall of the through hole by vapor deposition, and adjacent elements are connected in series. The number of elements connected in series is 6.

[0292] A UV curable resin (TB3118, available from ThreeBond Holdings Co., Ltd.) was applied with a dispenser (2300N, available from SAN-EI TECH Ltd.) in such a manner that the edge of the glass substrate was surrounded by the power generation region. Thereafter, the resultant was moved into a glove box whose internal environment was controlled to be low in oxygen concentration and the oxygen concentration was controlled to be 0.5%. A glass cover serving as a second substrate was placed on the UV curable resin, and the UV curable resin was cured by UV irradiation to seal the power generation region, thereby manufacturing Figure 5 The solar cell module 1 of the present disclosure is shown.

[0293] <Evaluation of Solar Cell Modules>

[0294] The IV properties of the obtained solar cell module 1 were evaluated by a solar cell evaluation system (As-510-PV03, obtained from NF Corporation) under the emission of a white LED controlled to 3,000 lux, thereby determining the initial open circuit voltage Voc1 (V) and the maximum output power Pmax1 (μW / cm 2 ). Similarly, the IV properties at 100 lux were evaluated to determine Voc2 and Pmax2. Subsequently, the solar simulator (AM1.5, 10 mW / cm 2 ) The solar cell module 1 was irradiated for 200 hours to evaluate the IV characteristics at 3,000 lux and 100 lux again to measure the open circuit voltage and the maximum output power after light irradiation at high light intensity to determine the respective retention rates. The results are presented in Table 2.

[0295] (Example 2)

[0296] Except that the distance between the first electrodes of adjacent photoelectric conversion elements and between the hole blocking layers was changed to 200 μm, Voc1, Pmax1, Voc2, Pmax2 and retention were obtained in the same manner as in Example 1. The structure of the module is presented in Table 1. The results are presented in Table 2.

[0297] (Example 3)

[0298] Except that the distance between the electron transport layers of adjacent photoelectric conversion elements was changed to 10 μm, Voc1, Pmax1, Voc2, Pmax2 and retention rate were obtained in the same manner as in Example 1. The structure of the module is presented in Table 1. The results are presented in Table 2.

[0299] [Table 1]

[0300]

[0301] (Example 4)

[0302] Voc1, Pmax1, Voc2, Pmax2 and retention were obtained in the same manner as in Example 3 except that 8 mg of a cobalt complex compound represented by Structural Formula 4 (FK102, available from Sigma-Aldrich) was added to the hole transport material.

[0303] (Example 5)

[0304] Voc1, Pmax1, Voc2, Pmax2 and retention were obtained in the same manner as in Example 3 except that 15 mg of a cobalt complex compound represented by Structural Formula 5 (FK209, available from Sigma-Aldrich) was added to the hole transport material.

[0305] (Example 6)

[0306] Voc1, Pmax1, Voc2, Pmax2 and retention were obtained in the same manner as in Example 3 except that 13mfg of a cobalt complex compound represented by Structural Formula 6 (FK269, available from Sigma-Aldrich) was added to the hole transport material. The results are presented in Table 2.

[0307] (Comparative Example 1)

[0308] Voc1, Pmax1, Voc2, Pmax2 and retention were obtained in the same manner as in Example 1, except that the first electrodes were formed so that the distance between the first electrodes of adjacent photoelectric conversion elements was 10 μm and then the hole blocking layer was formed.

[0309] (Comparative Example 2)

[0310] Voc1, Pmax1, Voc2, Pmax2 and retention rate were obtained in the same manner as in Example 1, except that the first electrode was formed in such a manner that the distance between the first electrodes of adjacent photoelectric conversion elements was 10 μm, then, the hole blocking layer was formed, and the distance between the electron transport layers and between the hole transport layers was changed to 10 μm. The results are presented in Table 2.

[0311] (Comparative Example 3)

[0312] The results are shown in Table 2, except that the distances between the electron transport layers and the hole transport layers of adjacent photoelectric conversion elements were changed to 10 μm.

[0313] (Comparative Example 4)

[0314] Voc1, Pmax1, Voc2, Pmax2 and retention were obtained in the same manner as in Example 2, except that the distance between the electron transport layers and the hole transport layers of adjacent photoelectric conversion elements was changed to 10 μm. The results are shown in Table 2.

[0315] [Table 2]

[0316]

[0317] From the results of Table 2, it is found that Examples 1 to 6 can suppress the decrease in output using light of low illuminance before and after exposure to light of high illuminance, compared with Comparative Examples 1 to 4. Specifically, the effect of improvement is significant under low illuminance light of 100 lux. In addition, it is found that Examples 4 to 6 in which a cobalt complex compound is added to a hole transport material have a higher retention rate than Examples 1 to 3.

[0318] As described above, in the solar cell module of the present disclosure, in at least two adjacent photoelectric conversion elements, the hole blocking layer is not connected, but the hole transport layer is connected. In other words, the solar cell module of the present disclosure includes a plurality of photoelectric conversion elements, wherein in at least two photoelectric conversion elements adjacent to each other, the hole blocking layer does not extend to each other but the hole transport layer is in a state of a continuous layer, wherein the hole transport layer extends to each other. Therefore, the solar cell module of the present disclosure hardly generates leakage current under light of high illuminance, and hardly damages the photosensitive compound. Therefore, it is possible to prevent the output from being reduced under light of low illuminance before and after being exposed to light of high illuminance. Therefore, the solar cell module of the present disclosure can have a high power output by utilizing light emitted from a light illuminance device (such as an LED and a fluorescent lamp) used indoors, even after being exposed to sunlight.

[0319] [Reference Symbol List]

[0320] 1: First substrate

[0321] 2, 2a, 2b: first electrode

[0322] 3: Hole blocking layer

[0323] 4: Electron transport layer

[0324] 5: Photosensitizing compounds

[0325] 6: Hole transport layer

[0326] 7, 7a, 7b: Second electrode

[0327] 8: Sealing components

[0328] 9: Second substrate

[0329] 10: Through-hole (conductive part)

[0330] 11: Sealing components

[0331] 101: Photoelectric conversion element

[0332] 102: Solar cell module

Claims

1. A solar cell module, include: A plurality of photoelectric conversion elements, Each photoelectric conversion element includes a first substrate, a first electrode, a hole blocking layer, an electron transport layer, a hole transport layer, a second electrode, a second substrate, and a sealing member, wherein the first electrode, the hole blocking layer, the electron transport layer, the hole transport layer, the second electrode, and the second substrate are formed on the first substrate, and the sealing member is disposed between the first substrate and the second substrate, and Among them, in at least two of the photoelectric conversion elements adjacent to each other, the hole blocking layers do not extend to each other, but the hole transport layers are in a state of a continuous layer, wherein the hole transport layers extend to each other.

2. The solar cell module according to claim 1, in, In at least two of the photoelectric conversion elements adjacent to each other, the first electrode in one photoelectric conversion element and the second electrode in the other photoelectric conversion element are electrically connected via the conductive portion of the hole transport layer penetrating through the continuous layer.

3. The solar cell module according to claim 1 or 2, in, In at least two of the photoelectric conversion elements adjacent to each other, the electron transport layers do not extend to each other.

4. The solar cell module according to claim 1 or 2, The electron transport layer is a porous layer formed of titanium oxide particles, wherein the photosensitive compound is adsorbed on the surface of the titanium oxide particles.

5. The solar cell module according to claim 1 or 2, The hole transport layer comprises a metal complex.

6. The solar cell module according to claim 5, The metal complex is a trivalent cobalt complex.